Pelatihan Peningkatan Kemampuan Terapi Wicara bagi Guru-guru Sekolah Khusus Bintang Harapan Kota Bandung - Nani Darmayanti; Inu Isnaeni Sidiq; Rosaria Mita Amalia (Jurnal Pengabdian Pada Masyarakat, 2022)
This Community Service (PPM) focuses on speech therapy training for teachers of students with autism syndrome at the Bintang Harapan Special School, Bandung City. That is a school that specifically educates students with autism. This is based on the fact that children with autism often find it difficult to communicate their desires both verbally (oral/speak) and non-verbally (gestures/gestures and writing) and teachers are required to have good skills and knowledge to handle these problems. Thus the purpose of this study is to increase the knowledge of teachers in dealing with or doing therapy for autistic children who have difficulty speaking. This activity was attended by 20 teachers at the Bintang Harapan Special School. The PPM method is carried out by means of lectures and pretest and posttest to measure the success of this activity. The results of the questionnaire show that after participating in the training through PPM, teachers have increased knowledge about therapy for students with autism. After attending the training, the posttest results showed that there was an increase in the teacher's understanding of speech therapy for autistic children from before and after attending the training. Before the training, teachers were generally able to answer 3-5 correct answers out of 10 questions given. Meanwhile, after the training was carried out, the teachers showed an increased level of knowledge and understanding, namely being able to answer 7-9 correct answers out of 10 questions given.